The fluoride effect (NaF) on germination and yield production of three local species of Poaceae fodder - Slimani S.; Boudelaa M.; Ladjama A.; Nadjeh I.; Benkadour M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The effect of fluoride (NaF) of three local species of rye grass (Lolium multiflorum Lamk., tall fescue (Festuca arundinaceae) and red canary grass (Phalaris arundinaceae) was analyzed at the concentration of 0; 10-1M; 10-2 M and 10-3M. The results showed that germination was effected by fluoride pollution. In fact, applying constant level of NaF caused considerable decrease in germinal capacity and power. At the concentration level of NaF solution over 2.33 g.l-1. The process of germination was completely inhibited in the three studied species. Moreover, it is worth mentioning that fluoride was found to greatly affect fescue growth. In contrast, fluoride had a favorable effect on rye grass and reed canary grass growth. Such growth stimulation is explained by an elevation in the respiratory activity. On the other hand, biochemical estimations show that fluoride treatment disturb biosynthesis of both photoreceptor pigments and sugars. Finally, we can conclude that the response of these ecotypes to fluoride pollution seems to be relatively resistant to this type of pollution.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)